Moodtopia : tame your moods, de-stress, and find balance using herbal remedies, aromatherapy, and more - Silverstein, Sara-Chana; Golant, Susan K. (Da Capo Lifelong, 2018)
"A popular herbalist's remedies and prescriptive program for emotional balance and overall health, using natural solutions such as essential oils, aromatherapy, and more Sara Chana Silverstein a lactation consultant and mom to seven kids. She is also a go-to herbalist who specializes in walking women through a focused herbal regimen to nourish their livers, refresh and revitalize their systems, and stabilize their moods. The goal? A balanced lifestyle. With tools, tips, and strategies, this is a practical, easy-to-use guide to herbs and homeopathy. Silverstein shares the best natural remedies to help combat stress, anxiety, and promote peace of mind and general health. She shows how herbs, aromatherapy, and other natural remedies are a gentle, natural way to enhance your emotional state without having to resort to antidepressants, anti-anxiety pills, or other medications that may have unwanted side effects. Silverstein's dedicated program teaches women to harness the power of aromatherapy (different aromas help with different ailments), color therapy, diet, and other mood-enhancing tools to lead to optimal emotional and mental wellness"--